Neurological disorders in patients with bullous pemphigoid: clinical and experimental investigations. (4th February 2015) - Gambichler, T.; Segert, H.; Höxtermann, S.; Schmitz, L.; Altmeyer, P.; Teegen, B.
Abstract Background Previous studies have shown that patients with bullous pemphigoid (BP) are more likely to have neurological diseases (ND). Objectives To compare clinical findings in BP patients with and without ND and to investigate BP180 autoantibody binding in different neuronal tissues of mammalians. Methods Our database was searched for clinical findings of in‐patients with the definitive diagnosis of BP. Moreover, brain tissue of mammalians was treated with serum of BP patients with elevated BP180 autoantibodies using biochip mosaics. Results Of 85/161 (52.8%) patients had a history of at least one ND (BP+ND). BP180 (P = 0.018), eosinophils (P = 0.043) and patients' accommodation in nursing homes (P < 0.0001) remained in the logistic regression model as significant independent predictors for the presence of ND in patients with BP. Subgroup analysis of community‐dwelling BP patients revealed 25/93 (26.9%) patients with ND. In this population, the presence of ND also significantly correlated with BP180 (r = 0.26; P = 0.0003) and eosinophils (r = 0.19; P = 0.0087). In the animal model, no BP180‐specific immunofluorescence could be detected. Conclusions Our data support results of previous studies detecting significantly increased frequency of ND in BP patients. We have shown that raised BP180 titres and blood eosinophils are independent predictors for the presence of ND in BP patients. However, our experimental data do not support previous results indicating that specific binding of BP180 antibodies in neuronal tissue plays a pathogenetic role in ND.